Process mapping improvement: extending value stream maps with waste identification diagrams - Dinis-Carvalho, José (2015)
Value Stream Mapping (VSM) is likely the most common tool to represent and analyse the value stream of product families. However, it has several limitations, recognized by professionals and academics, namely in terms of identification of certain types of waste (activities without added value). The purpose of this paper is to present a VSM extension based on elements coming from a new type of representation and analysis tool called Waste Identification Diagram (WID), which is being developed at the Production and Systems Department of University of Minho. WID is able to represent, in an effective manner, information about several aspects, including wastes related with production and people, layout, available capacity and even economic indicators. The inclusion of WID elements within traditional VSM was successfully achieved, resulting in a VSM extension which is more effective than the traditional VSM, not only in the information provided but also in terms of interpretation easiness.